PENDAMPINGAN KLASIFIKASI DAN PENYIAPAN BIAYA PRODUKSI SEBAGAI STRATEGI PENINGKATAN EFISIENSI OPERASIONAL USAHA - Nurjanah, Rina; Tikaromah, Oom; Yuliani, Reva; Purnama, Mega Lenita; Amalia, Fitria (Universitas katolik Musi Charitas, 2025)
Purpose: This community engagement program aimed to enhance the capacity of micro, small, and medium enterprises (MSMEs), particularly in the food sector, in understanding cost classification and systematically preparing production cost estimates. The intervention was intended to address efficiency-related challenges in production management, which are commonly faced by small-scale businesses. Design/Methodology/Approach: The program was implemented through several phases, including initial socialization, technical training, the application of simple technologies, intensive mentoring, and final evaluation. Each phase was designed to provide business partners with both conceptual understanding and practical skills in applying cost classification and production management principles. Findings: The results revealed a significant improvement in participants’ comprehension of cost structures and production management. MSME actors demonstrated greater accuracy and structure in classifying cost components, which directly contributed to enhanced operational efficiency and more informed business decision-making. Practical Implications: The program produced tangible outcomes by equipping participants with the ability to independently prepare production cost reports and income statements. The training and mentoring strengthened their financial management readiness in a more professional and sustainable manner. Originality/Value: This initiative offers an applicable and replicable approach to empowering MSMEs through strengthened financial and managerial literacy. The knowledge gained is expected to serve as a strategic asset in improving operational efficiency and competitiveness amid an increasingly dynamic market environment.